Annual Plans 1966-67 and 1967-68 Progress Report Gujarat State - Planning Commission (Planning Commission, 1966)
With the end of the Third Five Year Plan, the Fourth Five Year Plan period was to have commenced from 1st April, 1966. Pending the finalisation of the Fourth Plan, the progress of development was continued through the Annual Plans. In December, 1967, the National Development Council decided that the Fourth Five Year Plan shall commence from 1st April, 1969 and the period from 1966-67 to 1968-69 should be considered as Annual Plans period.
General Administration Department (Planning), Government of Gujarat